Combining functional diversity of lotic fish communities with river health assessment based on multi-metric chemical pollution and biological integrity index models - Jargal, Namsrai; Mamun, Md; Choi, Chang-Yun; An, Kwang-Guk (Frontiers in Environmental Science, 2022)
Trait-based functional studies are widely used to elucidate the relationships between ecological indicators and environmental parameters as well as to predict functional change in aquatic biota in response to various types of human disturbance. Clarifying how functional traits of aquatic organisms depend on environmental conditions can facilitate aquatic conservation and management, but determining the importance of these traits to ecological river health requires further investigation. As fish play a key role in the assessment of ecological conditions, we examined the relevance of functional diversity of lotic fish to the river health assessment using multi-metric models of water pollution (mWPI) and fish-based biological integrity (mIBI). Twelve fish traits related to food acquisition, environmental stability, and mobility were used for the functional analyses. Chemical river health was highly sensitive to downstream organic matter and nutrient pollution according to mWPI. Based on the present gradient of chemical health and water chemical variables, we identified three water quality groups (G-I, G-II, and G-III). G-I, G-II, and G-III showed low, intermediate, and high levels of water quality degradation, respectively. Spatially significant differences among these groups were observed for both the taxonomic and functional structures of lotic fish as well as ecological river health based on mIBI. The dominance of sensitive species was high in G-I, whereas tolerant and exotic species contributed strongly to the species compositions of G-II and G-III. Functional richness and dispersal were significantly reduced in G-III, and their decreases correlated with ecological health and the loss of species that are insectivorous, rheophilic, and sensitive to water pollution. Regarding redundancy analyses, both the models of functional trait metrics (F = 8.06, p < 0.001) and mIBI metrics (F = 4.88, p < 0.01) indicated good performance in terms of the variation in water quality and chemical river health parameters. Overall, the functional trait-based diversity of lotic fish is significant to the assessment of ecological river health and reflects water chemical quality. This association arises because niche occupation in functional space by all species, along with their abundance distribution, is highly responsive to the loss of species with sensitive traits due to water pollution.